Predicting Financial Distress in Chinese Firms - Cao, Chenyu (2016)
The development of the bankruptcy process for Chinese firms has had a great effect on the whole society since the enforcement of removal system for “distress firms” was applied in China’s stock market in 2001. With concern coming from all investors, practitioners, analysts and regulators, predicting firms in financial distress and offering an early warning for Chinese listed firms is becoming significantly more important. Directly applying the Z-score model and methodologies that developed in western countries to Chinese distress firms may not be practical, since there are distinct differences in accounting rules, the requirements of financial documents, the nature of firms and the corporate governance between the companies in the western world and in China. Therefore, a new model called Z-china Score was developed, aiming to identify and predict the distress firms.